Self-Realization of Students with Disabilities as a Basic Mechanism of Social Inclusion - Osmuk L.A (Moscow State University of Psychology and Education, 2018)
The problem covered in the article concerns the features of self-realization in students with disabilities. Self-realization is seen as the basic mechanism of social inclusion. For a disabled student, even the first attempts to demonstrate his/her potential may result in his/her successful inclusion in the educational environment contributing to an overall feeling of security. As an empirical material we use data of in-depth interview (n=12) conducted with students of the Institute of Social Technologies and Rehabilitation of Novosibirsk State Technical University; the results allow us to analyze the process of self-realization and its effects on the individual. The obtained variations of self-realization trajectories provide an opportunity to improve the work of the social and psychological support service of the Resource and Training Center taking into account the above mentioned mechanism. It is argued that self-realization is the starting point of motivation to self-inclusion.